(untitled) (Semiárida, 2020)
Winter forage deficit is a recurrent issue in rangelands of southern Brazil, generating nutritional deficiencies to herbivores kept in such conditions, being more decisive in shallow soils. We studied 12 combinations of fertilization and liming related to autumn grazing deferment of rangeland on shallow basaltic soil in order to accumulate forage for use in winter. No significant differences were (P<0,05) observed in total forage mass (MF) and green forage mass (MFV) as a function of treatment. A quadratic effect for MF and MFV according to the time of deferral, and the maximum accumulation occurred at 96 days (2965 Kg.ha-1 and 1446 Kg.ha-1, respectively). The dead material increased linearly with time. With multivariate analysis we can see that these variables were influenced by the soil depth of the plots. The greater depth were associated with higher MF and lower amount of bare ground. In plots of shallower soil (< 5 cm) ruderal species predominated, with forage value lower than what prevailed in deeper soils.